2020
DOI: 10.1136/bmjopen-2020-040290
|View full text |Cite
|
Sign up to set email alerts
|

Role of formative assessment in predicting academic success among GP registrars: a retrospective longitudinal study

Abstract: ObjectivesThe James Cook University General Practice Training (JCU GPT) programme’s internal formative exams were compared with the Royal Australian College of General Practitioners (RACGP) pre-entry exams to determine ability to predict final performance in the RACGP fellowship exams.DesignA retrospective longitudinal study.SettingGeneral Practice (GP) trainees enrolled between 2016 and 2019 at a Registered Training Organisation in regional Queensland, Australia.Participants376 GP trainees enrolled in the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…We located 11 studies including a correlation between an interview and SJT. We excluded four of these studies because we could not determine whether or how much range restriction affected the sample (Heggarty et al, 2020; Husbands et al, 2018), whether the interview was structured (Husbands et al, 2018; Yingling et al, 2018), or the constructs measured in the SJT were very different from the SJT constructs in the rest of the samples (i.e., emotional management SJT in Knorr et al, 2018). This left seven studies which included eight independent samples, which we describe in the following.Morgeson et al (2005) reported an uncorrected correlation of .23 between a structured interview and SJT in a sample of 90 job incumbents.…”
Section: Updates To Selection Methods Intercorrelationsmentioning
confidence: 99%
“…We located 11 studies including a correlation between an interview and SJT. We excluded four of these studies because we could not determine whether or how much range restriction affected the sample (Heggarty et al, 2020; Husbands et al, 2018), whether the interview was structured (Husbands et al, 2018; Yingling et al, 2018), or the constructs measured in the SJT were very different from the SJT constructs in the rest of the samples (i.e., emotional management SJT in Knorr et al, 2018). This left seven studies which included eight independent samples, which we describe in the following.Morgeson et al (2005) reported an uncorrected correlation of .23 between a structured interview and SJT in a sample of 90 job incumbents.…”
Section: Updates To Selection Methods Intercorrelationsmentioning
confidence: 99%
“…As such, it is different in that there are no "high-stakes" test-taking or decision-making, but rather individual assessments provide feedback that then allows the learner to analyze "their own performance, formulate concrete learning goals and demonstrably attain them", which is opposed to the previously discussed assessment structure where the assessment is the evidence of learning or the lack thereof ( [84], p. 211). Further reading in this area should be directed to [85][86][87][88].…”
Section: Concluding Thoughts and The Future Of Educational Psychometricsmentioning
confidence: 99%
“…There are many correlative or interrelated factors to the success of international students, both short-term and long-term, such as English pro ciency, nancial resources, coping strategies, self-e cacy, motivation, etc. Until now, there have been many investigations on practicable tactics to guide medical students to academic success [7][8][9]. However, studies on learning methods related to licensing exams are rare.…”
Section: Introductionmentioning
confidence: 99%